Trauma and Relationship Strain: Oral Histories With World Trade Center Disaster Responders. (October 2019) - Hammock, Amy C.; Dreyer, Rebecca E.; Riaz, Mishal; Clouston, Sean A. P.; McGlone, Ashlee; Luft, Benjamin
Existing models of couple functioning after trauma are primarily based on the experiences of returning military veterans. In this study, we conducted thematic analysis of a purposive sample of 49 oral histories of responders to the 9/11/01 terrorist attacks to understand how they navigated life with their spouses after the response experience. Use of multiple coders and analytic matrices increased analytic rigor. In the sample, 34.7% disclosed a posttraumatic stress disorder (PTSD) diagnosis and another 22.7% mentioned experiencing at least one trauma symptom. Most responders had not sought mental health intervention, relying instead on their spouses' caregiving. Responders reported limited disclosure to their spouses about the details of their 9/11/01 response work, which may have helped them cope emotionally with repeated 9/11/01 clean-up duties. Shared values regarding the common good and patriotism were important for maintaining an intimate relationship after 9/11/01, and helping partners understand and feel understood by each other.